PENGARUH DUA JENIS PUPUK HAYATI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine Max L. Merill) VARIETAS GEMA - Miftahurrohmah .; Wasito . (Universitas Islam Kadiri, 2017)
Soybean which grow well is determined by good cultivation with looking at the growth and evolution of the plant. Growth and evalution of plants can be affected Rhizobium and bio-fertilizers, therefore to get optimal production, need to balancedwith a these combination of treatments. The purpose of this research is to know the interaction of dose rhizobium and bio-fertilizer “Petrobio” on growth and production of soybean(Glycine max L. Merill) “Gema” varieties. This study was conducted in March until June 2017, in rice field of Suwaloh Village, Pakel District, Tulungagung Regency. The design used was Randomized Block Design (RAK) with two factors and repeated 3 times. The results showed that 1) the combination of Rizhobium dose treatment and the Petrobio fertilizer showed very significant on the varieties of leaves number 21 and 28 days after plan, number of pods and dry weight of seeds; 2) there is no interaction of Rhizobiumand bio-fertilizer “Petrobio” on all parameters of observation in plant height, number of leaves, stem diameter; 3) Rizhobium dose treatment had a very significant effect on plant height 28 days after plan; 4) Rizhobium dose treatment had significant effect on high variable 21 days after plan; 5) Treatment combination showed the best result that is 12,55 gram.